Manajemen: Paradigma Baru dalam Menghadapi Perubahan - Soekarso, Soekarso (Bina Nusantara University, 2007)
Today’s leaders and/or managers must deal with a continual and rapid change. In deciding a major decision manager can no longer refer back to an earlier developed plan for its direction. Management techniques must continually notice changes in the environment and organization, assess, and manage changes. Managing change does not mean controlling, it rather than understanding it, adapting to it where necessary, and guiding it when possible. Business development nowdays comes to globalization era and present a speed growth suitable to the dynamic changing. That is why it based on a needs the professional management system the new paradigm basic changing which is oriented on effective target and resource efficient to achieve the goals.